2019
DOI: 10.5005/jp-journals-10071-23219
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation-assisted Bronchoscopy in High-risk Hypoxemic Patients

Abstract: Background and aims Hypoxemic patients undergoing fiber-optic bronchoscopy (FOB) are at risk of worsening of respiratory failure requiring mechanical ventilation due to FOB procedure itself and its complications. As patients with respiratory failure are frequently managed by non-invasive ventilation (NIV); feasibility of FOB through NIV mask has been evaluated in some studies to avoid intubation. We describe here our own case series. Materials and methods Clinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Higher incidence of nose pain reported in the NIV group could have been due to need of manipulation of the scope to reach up to the nostrils from the sealed opening of the face mask 27 37. None of the other adverse events reported in our study was significantly different in the three groups, which probably is due to intensive screening, and monitoring of the cases 17…”
Section: Discussionmentioning
confidence: 54%
“…Higher incidence of nose pain reported in the NIV group could have been due to need of manipulation of the scope to reach up to the nostrils from the sealed opening of the face mask 27 37. None of the other adverse events reported in our study was significantly different in the three groups, which probably is due to intensive screening, and monitoring of the cases 17…”
Section: Discussionmentioning
confidence: 54%
“…Endobronchial brushings or endobronchial biopsies are more rarely reported in critically ill patients ( 36 ). Transbronchial biopsies increase the risk for pneumothorax ( 37 ) and in patients on positive pressure ventilation could lead to tension pneumothorax; thus, they are likely not appropriate for research purposes. Because of the lack of published data with these specimen types, with the exception of protected specimen brushes, the committee focused on the safety and collection of BAL samples.…”
Section: Resultsmentioning
confidence: 99%
“…Sircar et al . report on 27 patients with respiratory failure who underwent bronchoscopy with NIV support, without requiring intubation ( 22 ). Baumann et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia is accepted as a risk factor for bronchoscopy-related complications, and especially for worsening hypoxemia and cardiac pathologies ( 22 ). In the present study, the complication group patients showed lower PaO 2 /FiO 2 than the patient group without complications.…”
Section: Discussionmentioning
confidence: 99%